2022
DOI: 10.1186/s12879-022-07211-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on infectious disease hospitalizations of neonates at a tertiary academic hospital: a cross-sectional study

Abstract: Background To investigate the impact of the coronavirus disease 2019 (COVID-19) pandemic on hospitalizations for neonatal infectious diseases. Methods We analyzed data for neonatal inpatients admitted at a tertiary academic hospital with a principal diagnosis of an infectious disease during January 2015 to December 2020. We compared hospitalizations in 2020 (COVID-19 cohort), corresponding with the impact of COVID-19 pandemic and associated contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…It may seem surprising at first sight that during the partial lockdown period, on average, the general health of both adolescents and parents included in this research improved. However, this confirms some known data, namely that during this period, various infectious diseases such as tuberculosis and legionellosis declined, due to the limitation of interpersonal contacts and therefore, the risks of contamination ( (accessed on 12 March 2022)) [ 31 , 32 ]. In addition, the widespread use of masks, hydro-alcoholic gels, and social distancing certainly also had an impact beyond the prevention of COVID-19 alone.…”
Section: Discussionsupporting
confidence: 87%
“…It may seem surprising at first sight that during the partial lockdown period, on average, the general health of both adolescents and parents included in this research improved. However, this confirms some known data, namely that during this period, various infectious diseases such as tuberculosis and legionellosis declined, due to the limitation of interpersonal contacts and therefore, the risks of contamination ( (accessed on 12 March 2022)) [ 31 , 32 ]. In addition, the widespread use of masks, hydro-alcoholic gels, and social distancing certainly also had an impact beyond the prevention of COVID-19 alone.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, we focused on the impact of COVID-19 countermeasures on diseases that have been under surveillance regimens for a long period of time, such as pediatric infections. However, it has been reported that cases of notifiable infectious diseases such as influenza and norovirus decreased in some countries during the COVID-19 pandemic period [ 3 , 4 , 5 , 6 , 7 ]. These reports do not necessarily verify the overall effect of these countermeasures on infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These two areas are distinct in that Osaka is a metropolitan area, and Iwate is situated in the northeast of Japan, with different populations and numbers of COVID-19 patients. Although there have been reports on specific diseases and institutions, such as the low prevalence of influenza during the COVID-19 pandemic [ 3 , 4 , 5 , 6 , 7 ], we targeted pediatric infectious diseases under surveillance to clarify the countermeasures in society. We evaluated the effectiveness and limitations of the infection control measures implemented at the societal level.…”
Section: Introductionmentioning
confidence: 99%
“…It has then decreased the utilization of basic maternal, neonatal, and children’s health care services [ 22 ] and poignantly sparked a new normal for neonatal mortality in developing countries [ 2 , 22 , 23 ]. Studies revealed the pandemic has positively impacted the epidemiology of neonatal sepsis in India [ 24 ], Bangladesh, Nigeria, South Africa [ 25 ], Saudi Arabia [ 26 ], Malawi, and rural Uganda [ 27 ], but had no significant impact in China [ 28 ] and Turkey [ 29 ]. Likewise, the impacts of the COVID-19 stringent index on the epidemiologic features of neonatal sepsis were not well documented in these countries and were largely unknown in the neonatal population, including Ethiopia [ 23 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the recent fragility of the epidemiology of neonatal sepsis, the authors of this article intended to model it using data from hospitals that thought to be free of recall bias [ 14 ] and to underline its relationship with COVID-19-impacted periods in Ethiopia. In Ethiopia, the national-wide lockdown policy was launched in April 2020 but gradually lifted [ 28 , 32 , 33 ] and replaced by the COVID-19 government’s stringent index or containment measures (neonatal visiting limitations, wearing a face mask, effective hand washing, physical distancing, and vaccination) [ 23 , 30 , 31 ]. These containment measures were announced in mid-March 2020 and widely publicized in April 2020 in Ethiopia [ 34 ].…”
Section: Introductionmentioning
confidence: 99%